Penerapan Teknologi Chatbot Whatsapp untuk Meningkatkan Pelayanan dan Jaringan Bisnis - Fahmi Ajismanto; Guntoro Barovih (Penerbit Goodwood, 2022)
Purpose: SMEs is one of the drivers Indonesian economy.Â Hence, SMEs must have a good customer service. Service is an important aspectÂ in business activities. Excellent service is the spearhead in capturing opportunities and understanding clients from the products and services offered. If the service provided is satisfactory and friendly, the client will continue to use the services we offer. The purpose of this community service activity is to increase the application of science and technology which can help the partners of the SME community of Asyik Suka in an effort to increase the productivity of product sales by improving customer service using chatbot tools, Method: To be able to improve services by implementing Artificial Intelligence (AI) in the form of chatbots that replace customer service to serve questions about service products offered by business people. The application of chatbots can help consumers learn about the products offered. By utilizing Chatbot, business people are able to provide services to customers for 24 hours, this chatbot technology can also save service costs and improve the quality of customer experience. Apart from that, Chatbots are also able to increase sales targets and support lead generation. This service activity provides knowledge and training on how to use chatbots for business actors. Results: Participants understand the service method with the application of Chatbot and its benefits, understand how to inimanage creating and implementing Artificial Intelligence (AI) in the form of chatbots and social media support applications, and PKM participants can understand the various types of advantages of using chatbot technology through the features/menus on the menu. Applications and their functions. Conclusion: The positive response from the participants that join this public service indicate this PKM is able to activate the SME Asyik Suka Community to improve their service. Also improvement of using chatbot science application and technology to help business process, especially on the product services.